Influence of root canal sealer on the bond strength of intraradicular posts cemented with resin cements: A literature review (Research, Society and Development, 2025)
The aim of this literature review was to investigate the influence of root canal sealers on the bond strength of intraradicular posts to dentin when cemented with resin cements. A total of 33 scientific articles were selected, including one systematic review and 32 laboratory studies, 5 of which used the pull-out test and 27 the push-out test. Most studies used extracted human teeth (27 studies), while 5 used bovine teeth. In total, the review encompassed 21 types of root canal sealers. Based on this literature review, it can be concluded that the root canal sealer influences the bond strength of posts cemented with resin cements and that the timing of post cementation may alter this property. Overall, canals sealed with epoxy resin-based sealers showed the best bond strength results, while those using eugenol-based sealers exhibited the lowest values. Calcium hydroxide-based sealers generally demonstrated favorable results, whereas calcium silicate-based sealers were found to be less favorable.